2008 IEEE International Conference on Software Testing Verification and Validation Workshop 2008
DOI: 10.1109/icstw.2008.43
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Validating the Quality of Specifications

Abstract: Model-based testing of state based systems is known to be able to spot non-conformance issues. However, up to half of these issues appear to be errors in the model rather than in the system under test. Errors in the specification at least hamper the prompt delivery of the software, so it is worthwhile to invest in the quality of the specification. Worse, errors in the specification that are also present in the system under test cannot be detected by model-based testing. In this paper we show how very desirable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…However, existing approaches for programming GUI applications are very different from the iTask paradigm (see Section 5). Earlier experience in using the iTask system to create an interactive application to explore extended state machine specifications [7] suggested that the iTask paradigm is suited to define GUI applications. However, essential features for defining GUIs are lacking in the current iTask system.…”
Section: Introductionmentioning
confidence: 99%
“…However, existing approaches for programming GUI applications are very different from the iTask paradigm (see Section 5). Earlier experience in using the iTask system to create an interactive application to explore extended state machine specifications [7] suggested that the iTask paradigm is suited to define GUI applications. However, essential features for defining GUIs are lacking in the current iTask system.…”
Section: Introductionmentioning
confidence: 99%